Regiospecific Synthesis of 1‐Trifluoromethylisoquinolines Enabled by Photoredox Somophilic Vinyl Isocyanide Insertion. Issue 13 (11th September 2014) - Cheng, Yuanzheng; Yuan, Xiangai; Jiang, Heng; Wang, Ruzhi; Ma, Jing; Zhang, Yan; Yu, Shouyun
Abstract A strategy has been developed for the regiospecific synthesis of 1‐trifluoromethylisoquinoline derivatives. This strategy is enabled by a photoredox vinyl isocyanide insertion with the help of Umemoto's reagent. The methodology presented here provides an access to highly fuctionalized 1‐trifluoromethylisoquinolines regiospecifically under mild conditions in good‐to‐excellent chemical yields. A detailed mechanism is proposed, which is supported by experiments and theoretical calculations. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>